Analisis Tingkat Kognitif Pada Soal LKS SMP Kelas 8 Berdasarkan Taksonomi Bloom Revisi - Fitriani, Melia Sari; Susanta, Agus; Agustinsa, Ringki; Utari, Tria (JP2MS, 2021)
This study aims to determine the cognitive level of the questions on the LKS SMP grade 8 based on the revised bloom taxonomy. This type of research is descriptive with a qualitative approach. The type of research used is descriptive with a qualitative approach. Sources of data in this study are the total number of questions on the flat-sided shape of the math worksheets for class 8 semester 2 on the material of flat-sided shapes. The results of this study show that of 42 questions C1 (Remember) of 9,524% with a cognitive process of "Naming and Demonstrating", category C2 (Understanding) of 9,524% with cognitive processes of "Counting", category C3 (applying) of 64.3% with process cognitive "Applying, Executing and Implementing", category C4 (Analyze) by 16.67% with a cognitive process of "Analyzing and Organizing", category C5 (Evaluating) by 0%, category C6 (Creating) by 0%. From the results of the study it can be concluded that the questions on this worksheets have not met the ideal percentage of the cognitive level based on the 2013 curriculum. Keywords : Cognitive Level, LKS, Revised Bloom's Taxonomy